The impact of young radio jets traced by cold molecular gas. Issue 9 (27th October 2021) - Morganti, Raffaella; Oosterloo, Tom; Murthy, Suma; Tadhunter, Clive
Abstract: Ranging from a few pc to hundreds of kpc in size, radio jets have, during their evolution, an impact on their gaseous environment on a large range of scales. While their effect on larger scales is well established, it is now becoming clear that they can also strongly affect the interstellar medium (ISM) inside the host galaxy. Particularly important is the initial phase ( < 10 6 years) of the evolution of the radio jet, when they expand into the inner few kpc of the host galaxy. Here we report on results obtained for a representative group of young radio galaxies using the cold molecular gas as a tracer of jet‐ISM interactions. The sensitivity and high spatial resolution of ALMA and NOEMA are ideal to study the details of this process. In many objects, we find massive molecular outflows driven by the plasma jet, even in low‐power radio sources. However, the observed outflows are limited to the circumnuclear regions and only a small fraction of the ISM is leaving the galaxy. Beyond this region, the impact of the jet seems to change. Fast outflows are replaced by a milder expansion driven by the expanding cocoon created by the jet‐ISM interaction, resulting in dispersing and heating the ISM. These findings are in line with predictions from simulations of jets interacting with a clumpy medium and suggest a more complex view of the impact of AGN than presently implemented in cosmological simulations.